2020
DOI: 10.1002/pros.23980
|View full text |Cite
|
Sign up to set email alerts
|

Corpora amylacea in benign prostatic acini are associated with concurrent, predominantly low‐grade cancer

Abstract: Background: Corpora amylacea (CAM), in benign prostatic acini, contain acutephase proteins. Do CAM coincide with carcinoma?Methods: Within 270 biopsies, 83 prostatectomies, and 33 transurethral resections (TURs), CAM absence was designated CAM 0; corpora in less than 5% of benign acini: CAM 1; in 5% to 25%: CAM 2; in more than 25%: CAM 3. CAM were compared against carcinoma presence, clinicopathologic findings, and grade groups (GG) 1 to 2 vs 3 to 5.The frequency of CAM according to anatomic zone was counted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…We observed pCR-positive deposits not only in benign acini but also in cancer acini. Although CAs are primarily noted in benign acini, they have been identified in 0.4%-13% of cancer acini [49]. Therefore, the observation of amyloid-forming deposits in the lumen of cancer acini is not surprising; however, it is noteworthy that neither the tumor glands nor their luminal deposits were immunoreactive to lactoferrin.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We observed pCR-positive deposits not only in benign acini but also in cancer acini. Although CAs are primarily noted in benign acini, they have been identified in 0.4%-13% of cancer acini [49]. Therefore, the observation of amyloid-forming deposits in the lumen of cancer acini is not surprising; however, it is noteworthy that neither the tumor glands nor their luminal deposits were immunoreactive to lactoferrin.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests a common mechanism underlying the formation of CAs in the lungs and prostate. CAs are frequently identified in normal prostate tissue [49], and their presence does not appear to damage the surrounding tissues in the prostate and lung. Thus, we can speculate that CAs in these organs are formed for physiological reasons rather than serving a pathological function.…”
Section: Discussionmentioning
confidence: 99%
“…In the human prostate, CA occurrence with aging (Klimas et al, 1985; Sfanos et al, 2009; Shakya et al, 2003) has been reported, but its origin is not fully elucidated. Studies reported associations of epithelium damage, chronic and acute inflammation, and urinary retention (Cross et al, 1992; Klimas et al, 1985; Palangmonthip et al, 2020; Sfanos et al, 2009). The presence of glycoconjugates suggests its formation partially by prostatic secretion (Morales et al, 2005) which is in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is reasonable to suggest that CA formation may also be related to changes in metabolism, which is altered during prostate carcinogenesis. In addition, CA deposition was described in 55% of high‐grade PIN cases (Bostwick et al, 1993) as well as hyperplasia and prostate carcinoma (Christian et al, 2005; Palangmonthip et al, 2020). Thus, the decrease of CA incidence may be due to the MLT protective role against oxidative damage, including the increase of GST activity, which avoided tissue dysfunction over time.…”
Section: Discussionmentioning
confidence: 99%
“…Corpora amylacea (starch-like bodies) and calculi are luminal bodies commonly present in benign prostatic acini [117,118] and in prostate [117][118][119][120][121][122][123][124]; they are also found in approximately 25% of men aged between 20 and 40 years [122]. Amyloid formation by the pro-inflammatory S100A8/A9 proteins has been detected in the ageing prostate [125][126][127][128][129].…”
Section: Amyloidosismentioning
confidence: 99%